Hold your breath: A new index of air quality - Andreas Buehn; Mohammad Reza Farzanegan (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
Environmental quality and climate change have long attracted attention in policy debates. Recently, air quality has emerged on the policy agenda. We calculate a new index of air quality using CO2 and SO2 emissions per capita as indicators and provide a ranking for 122 countries from 1985 to 2005. The empirical analysis supports the EKC hypothesis and shows a significant influence of determinants such as energy efficiency, industrial production, electricity produced from coal sources, and urbanization on air quality. According to our index, Luxemburg, Norway, Iceland, Switzerland, and Japan are among the top 5 countries in terms of air quality performance. The Democratic Republic of Congo, Eritrea, Ethiopia, Togo, and Nepal performed worst in 2005.
Keywords: Q56; Q58; 330; Air quality; MIMIC model; EKC hypothesis; Development; Emissions; Luftverunreinigung; Luftreinhaltung; Sozialer Indikator; Kohlendioxid; Schwefeldioxid; Environmental Kuznets Curve; Welt